The Implementation of Project Based Learning in the English Course - Taqiya Nabila Prameswari; Fahriany; Faiha Salwa Labibah (EDULANGUE, 2024)
Teachers and lecturers exhibit a satisfactory comprehension of the project-based learning (PBL) method. However, there remains a deficiency in the requisite skills necessary for the proficient implementation of this pedagogical approach. Skill development is imperative to fully actualize the potential of PBL within the educational landscape. Consequently, this research serves as an example for the authentic implementation of PBL in the context of English language learning. Utilizing a methodology rooted in library research, the researcher amalgamates findings and theoretical frameworks related to project-based learning with the current educational landscape. Noteworthy is the contemporary shift in curriculum, emphasizing autonomous learning, fostering student activeness, and providing the flexibility to study at any time and place. The research meticulously delineates the method and its application in English language instruction. This detailed exposition aims to furnish educators with insights and inspiration for the judicious integration of the project-based learning method into their instructional practices. Key Words: Project-based Learning, English Course, Merdeka Belajar.